2016
DOI: 10.1007/s00484-016-1245-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity profile of 2014 FIFA World Cup players, with regard to different ranges of air temperature and relative humidity

Abstract: The present study attempts to assess changes in soccer players' physical activity profiles under the simultaneous influence of the different combinations of ambient temperature and relative humidity characterising matches of the 2014 FIFA World Cup hosted by Brazil. The study material consisted of observations of 340 players representing 32 national teams taking part in the tournament. The measured indices included total distances covered; distances covered with low, moderate, or high intensity; numbers of spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 50 publications
5
41
0
1
Order By: Relevance
“…Consequently, match analysis studies can provide useful information for coaches, who need significant, relevant, and easily gathered feedback to be successfully applied in training and competitive matches ( Hughes and Franks, 2004 ; Wright et al, 2013 ). Today, technologically advanced systems are commonly used for data gathering ( Castellano et al, 2014 ) based on the state-of-the-art algorithms along with video-recording technology to supply data on the physical (motion analysis) and technical and tactical (notational analysis) performance of soccer players ( Bradley et al, 2013 ; Konefał et al, 2019a ) with regard to their playing positions ( Andrzejewski et al, 2018 ) and contextual variables ( Chmura et al, 2017b ; Gai et al, 2019 ; Oliva-Lozano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, match analysis studies can provide useful information for coaches, who need significant, relevant, and easily gathered feedback to be successfully applied in training and competitive matches ( Hughes and Franks, 2004 ; Wright et al, 2013 ). Today, technologically advanced systems are commonly used for data gathering ( Castellano et al, 2014 ) based on the state-of-the-art algorithms along with video-recording technology to supply data on the physical (motion analysis) and technical and tactical (notational analysis) performance of soccer players ( Bradley et al, 2013 ; Konefał et al, 2019a ) with regard to their playing positions ( Andrzejewski et al, 2018 ) and contextual variables ( Chmura et al, 2017b ; Gai et al, 2019 ; Oliva-Lozano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research to date has indicated that the more difficult biometeorological conditions during a competition are, the harder it is to succeed (Mohr et al 2012, Chmura et al 2017a). The present study confirms these reports but also makes a novel observation that when matches take place in conditions of no thermal stress (NTS), the biometeorological conditions at training centres also prove to be significant for the match outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analyses showed that the longest recorded mean distance (10.5 km) was covered by players in an air temperature below 22°C and relative humidity below 60%, while the shortest (9.8 km) was covered in the same air temperature range, but with relative humidity above 60%. Significant differences in the number of sprints performed by players were found between the air temperature ranges below 22°C (41 performed sprints) and above 28°C (31), but only at the relative humidity below 60% (Chmura et al 2017a). What is more, Nassis et al (2015) found that while the numbers of passes did not differ, the pass accuracy was higher under high, rather than low, environmental stress conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Scientific publications describe measurements of indoor air quality. They were conducted in didactic rooms (Asif et al 2018;Chmura et al 2017;Hwang et al 2017;Kviesis et al 2017;Marć et al 2018;Śmiełowska et al 2017). In most publications, the evaluation of the results was based on a Fig.…”
Section: Discussion Of Researchmentioning
confidence: 99%